A systematic review of diabetic foot infections: pathogenesis, diagnosis, and management strategies - Maity, Sabyasachi; Leton, Noah; Nayak, Narendra; Jha, Ameet; Anand, Nikhilesh; Thompson, Kamala; Boothe, Danielle; Cromer, Alexandra; Garcia, Yaliana; Al-Islam, Aliyah; Nauhria, Samal (Frontiers in Clinical Diabetes and Healthcare, 2024)
BackgroundDiabetic foot infection represents a significant complication of diabetes mellitus, contributing substantially to morbidity, mortality, and healthcare expenditure worldwide. Accurate diagnosis relies on a comprehensive assessment integrating clinical evaluation, imaging studies, and microbiological analysis. Management necessitates a multidisciplinary approach, encompassing surgical intervention, antimicrobial therapy, and advanced wound care strategies. Preventive measures are paramount in reducing the incidence and severity, emphasizing patient education, regular foot screenings, and early intervention.MethodsThe researchers performed a systematic review of literature using PUBMED MESH keywords. Additionally, the study was registered in the International Prospective Register of Systematic Reviews at the Center for Reviews and Dissemination, University of York (CRD42021277788). This review provides a comprehensive overview of the microbial spectrum and antibiotic susceptibility patterns observed in diabetic foot infections.ResultsThe search through the databases finally identified 13 articles with 2545 patients from 2021 to 2023. Overall, the predominant Gram-positive microbial species isolated were Staphylococcus aureus, Enterococcus fecalis, Streptococcus pyogenes, Streptococcus agalactiae, and Staphylococcus epidermidis. Whereas the predominant Gram-negative included Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis and Pseudomonas aeruginosa.ConclusionDiabetic foot infections represent a complex and multifaceted clinical entity, necessitating a holistic approach to diagnosis, management, and prevention. Limited high-quality research data on outcomes and the effectiveness of guideline recommendations pose challenges in updating and refining existing DFI management guidelines.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021277788, identifier CRD42021277788.